UDK: 31.362.3 SAFETY STUDIES IN SOYBEAN OIL PRODUCTION PROCESS - khamdamov, muzaffar (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
Annotation. Strictly following the specific procedures for each operation is crucial to producing top-quality soybeans. Achieving this quality necessitates on-farm quality control during post-harvest processing. To enhance the soybean aspiration process, employing a grid with slanted holes in the aspiration zone and a specialised fan can effectively remove both light and heavy impurities.